The chronological order and the structural order in the legal thought of Spinoza (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This research is about the law, fairness and justice order in the philosopher Baruch Spinoza´s thought. We are going to examine some main points of Spinoza´sthought and also we are going to see the attractive and full of suggestions transfer ofthis questions to the rule´s application and the own purpose of law.
Keywords: thought´s structural; interpret and comprehend; chronological order and structural order; justice distribution